Пост: роман / Д. А. Глуховский ; худож. Н Хайдаров - Глуховский Дмитрий Алексеевич (АСТ, 2021)
Экземпляры: аб. (2021) / Инвентарный номер: 57354 / Цена: 553.70. / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 55 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6